SAT0198 How normal are the hands of normal controls? a study with dedicated magnetic resonance imaging. (1st June 2001) - Parodi, M; Dazzi, G; Silvestri, E; Garlaschi, G; Poggi, E; Cimmino, MA
Abstract : Background: Imaging of the joints is an invaluable technique for rheumatoid arthritis (RA). Magnetic resonance imaging (MRI) is increasingly used to visualise joint lesions in RA. 1 MRI is a very sensitive technique, which is able to show subtle changes of the joints. However, little is known about MRI findings in normal subjects. Objectives: Our study evaluated bone lesions, articular space and thickness of the synovial membrane in normal controls. Methods: 50 hands of 25 controls (19 women) with age range 31–88 years were studied. Four subjects had slight osteoarthritis of the first carpometacarpal joint: this joint was excluded from further evaluation. MRI of the hand was performed using a 0.2T dedicated device (Artoscan, Esaote, Genova, Italy). GE T1 and STIR sequences were used on the coronal and axial planes. Evaluated lesions included a) bone oedema; b) erosions; c) tenosynovitis, and d) thickness of the synovial membrane and effusion in 6 different areas of the wrist, as well as in the MCP and PIP joints. Results: Bone oedema was seen in one subject only. Bone erosions were seen in 9/25 controls (36%). They were more frequent in subjects older than 65 years (50% vs. 23%; ns). The localization of erosions in the normal hand was not different from that observed in RA. Tenosynovitis of the extensor and flexor tendons was seen in 2/25 (8%) and 4/25 (16%) of controls, respectively. It was more frequent in subjects older than 65 years (41.7% vs. 7.7%; p = 0.07). Erosions and tenosynovitis were not associated with manual labour. Joint space range was calculated in 14 different locations of the hand. No differences were found according to gender. In contrast, subjects aged more than 65 years showed an increased thickness of the synovial membrane at the radio-ulnar joint (p = 0.01) and in the intercarpal row (p = 0.002), and an increased joint space in the third (p = 0.03) and fifth (p = 0.04) MCP joints. Conclusion: Bone erosions and tenosynovitis are frequent findings in normal subjects. In contrast, bone oedema was seen in only one control and seems therefore to be a specific finding of arthritic joints. Age, but not sex or manual activity, was associated with these changes. Articular space in the MCP and PIP joints, and synovial membrane thickness in 6 different locations of the wrist were increased in elderly subject. Our results indicate that caution should be used in defining MRI changes as specific for arthritis and in interpreting the data of published studies. Sufficiently large control groups should be included in studies of the arthritic joints. Reference: Cimmino, et al . Semin Arthritis Rheum. 2000;30:180–95